Reducing Racial Disparities in Maternal Healthcare: A Midwifery Focus - Jenna A. LoGiudice PhD, CNM, RN, FACNM (SAGE Publishing, 2022)
When compared with other developed nations, the United States (U.S.) has the highest maternal mortality rate. Furthermore, in the U.S. Black women are dying during pregnancy or the postpartum period at a rate three times higher than that of white women. This disparity points to the question of why inequities in maternal healthcare exist and, of critical importance, what is being done to combat them. The stark reality is that systemic racism is at the core of these health disparities and must be addressed by both the individuals providing care and the healthcare systems themselves. The underpinnings of systematic racism in maternal healthcare, as well as ways to both dismantle this racism and move forward with constructive changes, are explained in this practice update. Specifically, the positive impact that midwifery care has on maternal health outcomes will be discussed.